Implementasi Beracara Secara Elektronik (E-Court) Dalam Perkara Perdata - Aris Priyadi (Faculty of Law, Universitas Wijayakusuma, 2021)
The application of civil procedural law in case examinations is currently taking place in a direction that must accommodate developments in community law. Currently, the Supreme Court in carrying out one of its functions, namely the regulatory function, has made several regulations to fill legal gaps, especially in matters of civil procedural law. This is due to advances in technological developments, especially in the field of informatics as well as the desire of the public to accelerate case resolution. Therefore, the Supreme Court issued several Supreme Court regulations and various other technical directives regulating the practice of proceeding in civil cases. One of them is the Supreme Court Regulation Number 1 of 2019 dated 6 August 2019 concerning the Administration of Cases and Trials electronically followed by the Decree of the Chief Justice of the Supreme Court Number: 129 / KMA / SK / VIII / 2019 concerning Technical Guidelines for Case and Trial Administration in Courts Electronically. In electronic trials (e-Court), from the registration stage to submitting claims, answers, replicas, duplicates, conclusions and decisions are made electronically. Meanwhile, the payment of court fees is made electronically through the virtual account procedure. With this procedure, it is hoped that the case examination can run according to the principles of simple, fast, low cost. However, the examination of civil cases in court electronically cannot be carried out if the parties do not agree to carry out a civil case examination at the trial electronically (e-Court) this is as regulated in Article 20 of Perma No.1 of 2019, so that the examination runs as usual face-to-face before a court session or in other words a conventional trial.Keywords: reform, civil procedural law, e-CourtPenerapan hukum acara perdata dalam pemeriksaan perkara saat ini terjadi pembaruan ke arah yang sudah harus mengakomodasi perkembangan hukum masyarakat. Pada saat ini Mahkamah Agung dalam melaksanakan salah satu fungsinya, yaitu fungsi pengaturan telah membuat beberapa regulasi untuk mengisi kekosongan hukum terutama dalam masalah hukum acara perdata. Hal ini disebabkan karena adanya kemajuan perkembangan teknologi terutama dibidang informatika serta keinginan masyarakat dalam percepatan penyelesaian perkara. Oleh sebab itu Mahkamah Agung menerbitkan beberapa peraturan Mahkamah Agung dan berbagai petunjuk teknis lainnya yang mengatur praktik beracara dalam perkara perdata. Salah satu diantaranya adalah Peraturan Mahkamah Agung Nomor 1 tahun 2019 tanggal 6 Agustus 2019 tentang Administrasi Perkara dan Persidangan secara elektronik yang diikuti dengan Surat Keputusan Ketua Mahkamah Agung Nomor : 129/KMA/SK/VIII/2019 tentang Petunjuk Teknis Administrasi Perkara dan Persidangan di Pengadilan Secara Elektronik. Dalam Persidangan secara elektronik (e-Court) mulai tahap pendaftaran sampai memasukkan gugatan, jawaban, replik, duplik, kesimpulan dan putusan dilakukan secara elektronik. Sedangkan mengenai pembayaran biaya perkara dilakukan secara elektronik melalui tata cara virtual account. Dengan tata cara yang demikian diharapkan pemeriksaan perkara dapat berjalan sesuai asas sederhana, cepat, biaya ringan. Akan tetapi pemeriksaan perkara perdata di persidangan secara elektronik tidak bisa dilaksanakan apabila para pihak tidak setuju dilaksanakannya pemeriksaan perkara perdata di persidangan secara elektronik ( e-Court) hal tersebut sebagaimana diatur dalam Pasal 20 Perma Nomor 1 tahun 2019, sehingga pemeriksaan berjalan seperti biasa dengan tatap muka di muka sidang pengadilan atau dengan kata lain persidangan secara konvensional.Kata kunci : pembaruan, hukum acara perdata, e-Court.